Description of Stroke Patients with History of Smoking Activities - Paulus Sugianto; Fatih Nugraha Abdillah; Isnin Anang Marhana; Fidiana Fidiana (Universitas Airlangga, 2022)
Highlight: Smoking raises the risk of cardiovascular disease, which can lead to stroke. A total of 33 stroke patients were selected from 579 samples. The results show some tendencies. The tendency of stroke patients with a history of activity to smoke can be explained for a number of reasons. ABSTRACT Introduction: Smoking is a habit of Indonesian society and can be found in many places. Smoking increases the risk of cardiovascular problems, which can lead to stroke. Objective: Provides an overview of stroke patients who smoke from January to December 2020. Methods: This retrospective, descriptive research used medical records and extra data from telephone interviews with patients. A non-probability purposive sampling strategy with a total sampling method is used in this investigation. The observed variables include age, gender, number of cigarettes consumed per day, length of smoking history, type of stroke, and comorbidity. Results: The sample consisted of 33 participants chosen among 579 stroke patients. The age range of 56–65 (39.4%) was found to be the most prevalent in the 33 samples, and the sex group was dominated by men (100%). Then, for the smoking habit, the highest number of cigarettes consumed per day was dominated by the group of 9-16 cigarettes per day (45.46%). The group dominates the long smoking history with a smoking history of 30-50 years (42.43%). Ischemic stroke, also known as cerebral infarction, was the most common type (78.79%) among the samples. Of the 33 samples of stroke patients who smoked, 4 (12.12%) experienced comorbidities, including coronary heart disease, diabetes mellitus, and essential thrombocytosis. Conclusion: Several factors describe the tendency of stroke patients with a smoking history.